Circulating Ghrelin Acts on GABA Neurons of the Area Postrema and Mediates Gastric Emptying in Male Mice - Cabral, Agustina (2017)
Ghrelin is known to act on the area postrema (AP), a sensory circumventricular organ located in the medulla oblongata that regulates a variety of important physiological functions. However, the neuronal targets of ghrelin in the AP and their potential role are currently unknown. In this study, we used wild-type and genetically modified mice to gain insights into the neurons of the AP expressing the ghrelin receptor [growth hormone secretagogue receptor (GHSR)] and their role. We show that circulating ghrelin mainly accesses the AP but not to the adjacent nucleus of the solitary tract. Also, we show that both peripheral administration of ghrelin and fasting induce an increase of c-Fos, a marker of neuronal activation, in GHSR-expressing neurons of the AP, and that GHSR expression is necessary for the fasting-induced activation of AP neurons. Additionally, we show that ghrelin-sensitive neurons of the AP are mainly g-aminobutyric acid (GABA)ergic, and that an intact AP is required for ghrelin-induced gastric emptying. Overall, we show that the capacity of circulating ghrelin to acutely induce gastric emptying in mice requires the integrity of the AP, which contains a population of GABA neurons that are a target of plasma ghrelin.